Grobišče Župna cerkev v Kranju Bloki. Terenske risbe 1969−1973 - Belak, Mateja (E-Monographiae Instituti Archaeologici Sloveniae, 2021)
Within the framework of the basic research project The Župna cerkev Cemetery in Kranj, intended for the publication and research of materials from archaeological excavations of the eponymous burial ground, digital primary forms of archival sources are presented. So far, we have published field journals, field drawings and anthropological diaries in six volumes, and the new e-publication shows sketching blocks with field drawings of planums and more than 1,500 graves excavated between 1969 and 1973.